Hepaticojejunostomy vs. Hepaticoduodenostomy after Excision of Choledochal Cyst in Paediatric Population- A Retrospective Study - Gagan Deep; Suhitha Gajanthody; Ashraf Ahmad; B Harishchandra (JCDR Research and Publications Pvt. Ltd., 2021)
Introduction: Choledochal cyst is a rare congenital anomaly of the bile duct with female predominance. Surgical excision of the choledochal cyst with hepaticoduodenostomy or hepaticojejunostomy is the standard of care in the last few decades. Many surgeons favour hepaticojejunostomy. Aim: To evaluate the outcomes of open hepaticoduodenostomy vs. hepaticojejunostomy procedure in excision of choledochal cyst in paediatric population. Materials and Methods: This was a retrospective cohort study conducted from January 2015 to December 2019 on data of 16 paediatric patients who underwent choledochal cyst excision with biliary reconstruction in a tertiary health institute. The data of these patients were collected from Medical Records Department (MRD) on type of surgery performed, mean operating time, postoperative hospital stay, the onset of oral feeds and complications associated with the surgery and were analysed and evaluated in July 2021. All statistical analyses were performed with Statistical Package for Social Sciences (SPSS) version 23.0. A p-value of <0.05 was considered as statistically significant. Results: A total of 16 patients (5 males and 11 females) were included, out of them 9 (56%) had undergone hepaticoduodenostomy and 7 (44%) had undergone hepaticojejunostomy. The most common type of choledochal cyst was Type 1 (n=7, 43.7%). Operative time was longer for the hepaticojejunostomy than the hepaticoduodenostomy (212.86±31.33 vs 88.89±15.16 min; p-value 0.001). Patients who underwent hepaticoduodenostomy early feeds were started as compared to the hepaticojejunostomy (2.22 vs 5.29 days; p-value 0.001). Hospital stay was longer with the hepaticojejunostomy than the hepaticoduodenostomy (14.71±7.76 days vs 8.11±4.48 days; p-value 0.05). There were three complications (biliary enteric fistula that opened into the anterior abdominal wall at the previous surgical site incision, jejunal stump formed the fistulous tract with high output bile leak and surgical site infection was noted) in total noted in both groups. Conclusion: The present study concluded that hepaticoduodenostomy had a better outcome in factors such as operating time, the onset of feeds and hospital stay than with the hepaticojejunostomy